Layered positive electrode material, preparation method thereof and sodium ion battery

By achieving double-point doping of the sodium layer and the transition metal layer in the positive electrode material of the sodium ion battery and covering the metal oxides on the surface, the problems of high residual alkali on the surface and poor circulation performance of the material are solved, and the stability and performance of the material are significantly improved.

CN119742326AActive Publication Date: 2025-04-01CENT SOUTH UNIV

Patent Information

Application Number
CN202411791438.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The surface residual alkali of the positive electrode material of existing sodium ion battery is high and is prone to side reactions with the electrolyte, resulting in poor thermal stability or poor circulation performance of the material.

Method used

Double-point doping of the sodium layer and the transition metal layer is achieved in the core of the sodium ion battery positive electrode material, and metal oxide is coated on the surface of the material to form a structure of the core and the cladding layer.

Benefits of technology

This method effectively reduces residual alkali on the surface of the material, inhibits side reactions with the electrolyte, improves the circulation performance and air stability of the material, and simplifies the process and is easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742326A_ABST
    Figure CN119742326A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of materials, and provides a layered positive electrode material and a preparation method thereof, and a sodium ion battery, the layered positive electrode material comprises an inner core and a coating layer located on the surface of the inner core; wherein the chemical general formula of the inner core is [NaMb] [Ni < x > Fe < y > Mn < z > N < k > O < 2 >], 0 lt; b < = 0.1, 0.1 < = x < = 0.5, 0.1 < = y < = 0.5, 0.2 < = z < = 0.6, 0lt; k < = 0.1, x + y + z = 1, and M is a sodium layer doping element; n is a doping element of the transition metal layer; and the coating layer is a metal oxide. The transition metal layer and the sodium layer are doped with elements and are coated with the metal oxide cooperatively, so that the structural stability of the sodium battery positive electrode material is improved jointly, the content of residual alkali on the surface of the sodium battery positive electrode material is effectively reduced, and the cycle performance and the rate capability of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and in particular relates to a layered positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Lithium-ion batteries have high energy density, long life and excellent rate performance. They dominate the portable electronic device market and also show great prospects in electric vehicles. However, the global distribution of lithium resources is uneven, and lithium prices have fluctuated greatly in recent years, which will limit its application in large-scale energy storage. Sodium and lithium have similar physical and chemical properties and abundant resource reserves, which makes sodium-ion batteries have greater application prospects. Among them, layered oxide materials are considered to be the most promising positive electrode materials for sodium-ion batteries because of their easy preparation and high theoretical capacity. However, when layered oxide materials are used as the positive electrode of sodium-ion batteries, the crystal structure is not stable enough, and phase changes are prone to occur during the charge and discharge process, resulting in poor material performance. In addition, during the high-temperature solid-phase reaction of the nickel-iron-manganese ternary precursor and the sodium source, some sodium ions are released from the bulk phase of the material and remain on the surface of the particles, eventually forming residual alkali (the residual alkali is represented by Na 2 CO 3 The presence of residual alkali on the surface (in the form of NaOH and NaOH) will not only deteriorate the cycle stability of the positive electrode material, but also cause capacity decay.

[0003] Therefore, improving the structural stability of the material and reducing the residual alkali on the surface to prepare a sodium-ion battery cathode with excellent cycle performance and safety performance is of great significance for the large-scale application of sodium-ion batteries. As an effective modification method, ion doping can improve the stability of the crystal structure and inhibit the occurrence of harmful phase changes, thereby improving the cycle performance and rate performance of the material. For example, CN115924999A discloses a copper ion-doped nickel-iron-manganese-based ternary precursor, a preparation method and its application, by introducing copper elements in the preparation process of the nickel-iron-manganese ternary precursor, thereby significantly improving the material's cycle stability and air stability; CN112864389B discloses a sodium positive electrode material doped with at least one of Mn, Fe, Zn, Ag, Zr, Mo, Nb, Cu, Cr and Ti, improving the material's cycle performance and rate performance, significantly improving the sodium ion battery's charge and discharge capacity, specific capacity, cycle stability and service life; CN116885140A discloses a dual-point doping modification method, respectively doping and modifying the sodium layer and the transition metal layer, significantly improving the structural stability of the sodium positive electrode material, and then significantly improving the cycle performance of the sodium positive electrode material. Coating modification is also an effective modification method that can stabilize the material's crystal structure, prevent the detachment of the material's surface particles, and then improve the battery's cycle stability. For example, CN116169268A double-coated the surface of the layered oxide positive electrode material with metal oxide and carbon. By double-coating the layered oxide, the conductivity of the material is enhanced while its stability in the electrolyte is improved, and the leaching of transition metal elements is reduced, thereby improving the cycle stability of the material. However, some of the above methods only have a single sodium layer doping and transition metal doping. Even if double-point doping is achieved, the stability of the material structure can be improved, but the problems of high residual alkali on the surface of the material and easy side reactions with the electrolyte are difficult to solve, resulting in outstanding thermal stability and gas production problems of the material; while only single metal oxide coating can effectively reduce the surface residual alkali and prevent the occurrence of side reactions with the electrolyte, but the problem of unstable internal structure of the material during the long cycle charge and discharge process cannot be suppressed, resulting in poor cycle performance. Summary of the invention

[0004] The purpose of the embodiments of the present application is to provide a layered positive electrode material, which aims to effectively combine doping and coating modification methods to achieve all-round targeted modification of the positive electrode material of the sodium ion battery, and solve the problems existing in the prior art such as high residual alkali on the surface of the material, easy side reactions with the electrolyte, poor thermal stability of the material, or poor cycle performance.

[0005] The embodiment of the present application is implemented as follows: a layered positive electrode material, the layered positive electrode material comprising a core and a coating layer located on the surface of the core;

[0006] Among them, the chemical general formula of the core is [NaM b [Ni x Fe y Mn z N k O 2 , where 0 < b ≤ 0.1, 0.1 ≤ x ≤ 0.5, 0.1 ≤ y ≤ 0.5, 0.2 ≤ z ≤ 0.6, 0 < k ≤ 0.1, x + y + z = 1, M is a sodium layer doping element; N is a transition metal layer doping element; the coating layer is a metal oxide.

[0007] Preferably, M is one or more of Ca, Mg, Sr, La, K, Zn; N is one or more of Ti, Zr, Sb, Sc, Y, La, Ce, Sm, Ho, Ta.

[0008] Preferably, the metal oxide is one or more of zirconia, titanium oxide, tin oxide, magnesium oxide, tungsten oxide.

[0009] Preferably, the metal element in the metal oxide accounts for 0.05% - 0.5% of the mass of the core.

[0010] The embodiment of the present application also provides a preparation method of the above-mentioned layered cathode material, including:

[0011] Uniformly mixing the pre-sintered nickel iron manganese hydroxide with a sodium source, a sodium layer doping element, and a transition metal layer doping element, and performing a first sintering treatment to obtain a first-sintered sample;

[0012] After crushing the first-sintered sample, uniformly mixing it with a metal oxide, and performing a second sintering treatment to obtain a layered cathode material.

[0013] The embodiment of the present application also provides a sodium ion battery, and the sodium ion battery includes the above-mentioned layered cathode material.

[0014] The layered cathode material provided by the embodiments of the present application realizes double-site doping and co-deposition of metal oxides on the surface through the sodium layer and the transition metal layer, achieving the following effects: 1) The doping elements in the sodium layer play a supporting role in the sodium layer, stabilizing the layer spacing of the sodium layer before and after charge and discharge, making the charge and discharge curves of the battery smoother, and improving the cycling performance of the material; 2) By doping high-valence elements in the transition metal layer, the phase change (O3’→P3’) of the material during charge and discharge can be inhibited, improving the stability of the material, and thus improving the cycling performance of the material; 3) Coating the metal oxide on the surface of the material reduces the residual alkali on the surface of the cathode material, effectively inhibits the occurrence of side reactions with the electrolyte, and thus improves the cycling performance of the material; in addition, the coating layer provides a protective layer to prevent the cathode material from directly contacting and reacting with moisture and carbon dioxide in the air, improving the air stability of the material; 4) The process is simple and controllable, and is easy to mass-produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the SEM image of nickel-iron-manganese hydroxide provided by Embodiment 1 of the present application;

[0016] Figure 2 is the SEM image of the layered cathode material provided by Embodiment 1 of the present application. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0017] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application, and are not used to limit the present application.

[0018] The embodiments of the present application provide a layered cathode material, the layered cathode material includes a core and a coating layer located on the surface of the core;

[0019] Wherein, the chemical general formula of the core is [NaM b [Ni x Fe y Mn z N k O 2 , 0 < b ≤ 0.1, 0.1 ≤ x ≤ 0.5, 0.1 ≤ y ≤ 0.5, 0.2 ≤ z ≤ 0.6, 0 < k ≤ 0.1, x + y + z = 1, M is a doping element in the sodium layer; N is a doping element in the transition metal layer; the coating layer is a metal oxide.

[0020] Among them, 0.1 ≤ x ≤ 0.5, for example, it can be 0.1, 0.3 or 0.5; 0.1 ≤ y ≤ 0.5, for example, it can be 0.1, 0.3 or 0.5; 0.2 ≤ z ≤ 0.6, for example, it can be 0.2, 0.4 or 0.6, 0.4 ≤ a ≤ 1.2, for example, it can be 0.4, 0.6, 0.8, 1.0 or 1.2; 0 < b ≤ 0.1, for example, it can be 0.01, 0.05 or 0.1, preferably 0 < b ≤ 0.02; however, the above x, y, z, b are not limited to the listed values, and other unlisted values within the numerical range are equally applicable.

[0021] Among them, 0 < k ≤ 0.1, for example, it can be 0.0005, 0.001, 0.005, 0.01, 0.05 or 0.1, but it is not limited to the listed values, and other unlisted values within the numerical range are equally applicable, preferably 0 < k ≤ 0.01. This application represents the doping amount k of the doping element of the transition metal layer. Preferably, 0 < k ≤ 0.01. If k is too large, the specific capacity of the material will be significantly reduced.

[0022] In an alternative embodiment of the present application, the sodium layer doping element M is any one or a combination of at least two of the metal elements with a sodium ion radius similar to that of sodium ions. For example, it can be selected from one or several of Ca, Mg, Sr, La, K, Zn, and more preferably one or several of Ca, Mg, Sr.

[0023] In an alternative embodiment of the present application, N is any one or a combination of at least two of the high-valence elements such as Ti, Zr, Sb, Sc, Y, La, Ce, Ta, and more preferably one or several of Ti, Zr, Sb.

[0024] In an alternative embodiment of the present application, the metal oxide is one or several of zirconia, titanium oxide, tin oxide, magnesium oxide, tungsten oxide, and more preferably one or several of zirconia, titanium oxide, magnesium oxide.

[0025] In an alternative embodiment of the present application, the metal element in the metal oxide accounts for 0.05% - 0.5% of the core mass, preferably 0.05% - 0.3%.

[0026] The embodiment of the present application also provides a preparation method of the above-mentioned layered cathode material, including:

[0027] Uniformly mixing the pre-sintered nickel-iron-manganese hydroxide with a sodium source, a sodium layer doping element, and a transition metal layer doping element, and performing a first sintering treatment to obtain a first-sintered sample;

[0028] After crushing the first-sintered sample, uniformly mixing it with a metal oxide, and performing a second sintering treatment to obtain a layered cathode material.

[0029] In an optional embodiment of the present application, the precursor material nickel iron manganese hydroxide is subjected to a pre-sintering treatment, the pre-sintering temperature is 350-750° C., and the pre-sintering time is 3-9 hours.

[0030] In an optional embodiment of the present application, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium nitrate, sodium acetate, and sodium citrate, and the molar ratio of the sodium element in the sodium source to the sum of the nickel, iron and manganese elements in the nickel-iron-manganese hydroxide is (1-1.04):1.

[0031] In an optional embodiment of the present application, the nickel-iron-manganese hydroxide after pre-sintering is uniformly mixed with a sodium source, a sodium layer doping element and a transition metal layer doping element, and subjected to a single sintering treatment to obtain a sintered sample. The temperature of the single sintering treatment is 850-950°C, and the sintering time is 10-20h; the sintering atmosphere includes one or more of air and oxygen.

[0032] In an optional embodiment of the present application, the calcined sample is crushed, uniformly mixed with metal oxides, and subjected to a secondary sintering treatment to obtain a layered positive electrode material. The secondary sintering treatment temperature is 500-700°C, and the sintering time is 7-13h; the sintering atmosphere includes one or more of air and oxygen.

[0033] The above-mentioned layered positive electrode material and its preparation method and sodium ion battery are described in detail with specific examples as follows. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0034] Example 1

[0035] This embodiment provides a double-site doping and metal oxide coating synergistically modified O3 sodium layered positive electrode material, the double-site doping and metal oxide coating synergistically modified O3 sodium layered positive electrode material chemical formula is [NaCa 0.001 ][Ni 0.333 Fe 0.333 Mn 0.334 Ti 0.001 ]O 2 , wherein Ca is a sodium layer doping element, Ti is a transition metal layer doping element, and the coating layer includes zirconium oxide;

[0036] The preparation method of the double-point doping and metal oxide coating synergistically modified O3 sodium electric layered positive electrode material comprises the following steps:

[0037] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn0.334 (OH) 2 Pre-burning is performed, the pre-burning atmosphere is air, the pre-burning temperature is 550°C, the heating rate is 3°C / min, and the holding time is 6h to obtain a pre-burned material;

[0038] Step S2, mixing the pre-burned material obtained in step 1 with sodium carbonate, calcium oxide and titanium oxide through a high-speed mixer to obtain a high-mixed material, wherein the sodium content is 3% in excess, the calcium metal content is one thousandth of the sodium content, and the titanium metal content is one thousandth of the transition metal content; placing the high-mixed material in a box furnace, under an air atmosphere with an air flow rate of 16 L / min, heating to 900° C. at a heating rate of 3° C. / min, keeping the temperature for 15 hours, and then naturally cooling to room temperature to obtain a first-burned material; the first-burned material is mechanically crushed and vibrated to obtain a first-burned sample;

[0039] Step S3, weigh 100 kg of the calcined sample [NaCa 0.001 ][Ni 0.333 Fe 0.333 Mn 0.334 Ti 0.001 ]O 2 , and 0.3kg of zirconium oxide were added into a high mixer and mixed at 3000r / min for 15min. The mixture was placed in a box furnace and heated to 650℃ at a heating rate of 3℃ / min under an oxygen atmosphere. The mixture was kept warm for 6h and naturally cooled to room temperature. The sodium layered positive electrode material A1 was sieved through a 300-mesh sieve.

[0040] The SEM test of the sodium nickel iron manganese oxide positive electrode material prepared in this embodiment is as follows: Figure 1 shown.

[0041] Example 2

[0042] This embodiment provides a double-site doping and metal oxide coating synergistically modified O3 sodium layered positive electrode material, the double-site doping and metal oxide coating synergistically modified O3 sodium layered positive electrode material chemical formula is [NaMg 0.002 ][Ni 0.333 Fe 0.333 Mn 0.334 Zr 0.002 ]O 2 , wherein Mg is a doping element for the sodium layer, Zr is a doping element for the transition metal layer, and the coating layer comprises titanium oxide;

[0043] The preparation method of the double-point doping and metal oxide coating synergistically modified O3 sodium electric layered positive electrode material comprises the following steps:

[0044] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn0.334 (OH) 2 Pre-sintering is performed, the pre-sintering atmosphere is air, the pre-sintering temperature is 600°C, the heating rate is 3°C / min, and the holding time is 5h to obtain a pre-sintered material;

[0045] Step S2, the pre-burned material obtained in step 1 is mixed with sodium carbonate, magnesium oxide and zirconium oxide by a high-speed mixer to obtain a high-mixed material, wherein the sodium content is 3% in excess, the magnesium metal content is 0.2% of the sodium content, and the titanium metal content is 0.2% of the transition metal content; the high-mixed material is placed in a box furnace, under an air atmosphere, with an air flow rate of 16 L / min, and the temperature is first increased to 920° C. at a heating rate of 3° C. / min, and kept warm for 13 hours, and then naturally cooled to room temperature to obtain a first-burned material, and the first-burned material is mechanically crushed and vibrated to obtain a first-burned sample;

[0046] Step S3, weigh 100 kg of the burned sample [NaMg 0.002 ][Ni 0.333 Fe 0.333 Mn 0.334 Zr 0.002 ]O 2 , and 0.35kg of titanium oxide were added into a high mixer and mixed at 3000r / min for 15min. The mixture was placed in a box furnace and heated to 600℃ at a heating rate of 3℃ / min under an oxygen atmosphere. The mixture was kept warm for 8h and naturally cooled to room temperature. The sodium layered positive electrode material A2 was sieved through a 300-mesh sieve.

[0047] Example 3

[0048] This embodiment provides a double-site doping and metal oxide coating synergistically modified O3 sodium layered positive electrode material, the chemical formula of the double-site doping and metal oxide coating synergistically modified O3 sodium layered positive electrode material is [NaSr 0.002 ][Ni 0.333 Fe 0.333 Mn 0.334 Sb 0.001 ]O 2 , wherein Sr is a doping element for the sodium layer, Sb is a doping element for the transition metal layer, and the coating layer comprises magnesium oxide;

[0049] The preparation method of the double-point doping and metal oxide coating synergistically modified O3 sodium electric layered positive electrode material comprises the following steps:

[0050] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn 0.334 (OH) 2Pre-burning is performed, the pre-burning atmosphere is air, the pre-burning temperature is 500°C, the heating rate is 3°C / min, and the holding time is 8h to obtain a pre-burned material;

[0051] Step S2, mixing the pre-burned material obtained in step 1 with sodium carbonate, strontium oxide and antimony oxide through a high-speed mixer to obtain a high-mixed material, wherein the sodium content is 3% in excess, the calcium metal content is 0.2% of the sodium content, and the titanium metal content is 0.1% of the transition metal content; placing the high-mixed material in a box furnace, under an air atmosphere with an air flow rate of 16 L / min, heating to 880° C. at a heating rate of 3° C. / min, keeping the temperature for 20 hours, and then naturally cooling to room temperature to obtain a first-burned material; the first-burned material is mechanically crushed and vibrated to obtain a first-burned sample;

[0052] Step S3, weigh 100 kg of the calcined sample [NaSr 0.002 ][Ni 0.333 Fe 0.333 Mn 0.334 Sb 0.001 ]O 2 , and 0.25kg of magnesium oxide were added into a high mixer and mixed at 3000r / min for 15min. The mixture was placed in a box furnace and heated to 700℃ at a heating rate of 3℃ / min under an oxygen atmosphere. The mixture was kept warm for 5h and naturally cooled to room temperature. The sodium layered positive electrode material A3 was sieved through a 300-mesh sieve.

[0053] Comparative Example 1

[0054] The sodium layered positive electrode material B1 provided in this comparative example is not double-point doped and metal oxide coated. The chemical formula of the sodium layered positive electrode material O3 is NaNi 0.333 Fe 0.333 Mn 0.334 O 2 .

[0055] The preparation method of the O3 sodium layered positive electrode material comprises the following steps:

[0056] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn 0.334 (OH) 2 Pre-burning is performed, the pre-burning atmosphere is air, the pre-burning temperature is 550°C, the heating rate is 3°C / min, and the holding time is 6h to obtain a pre-burned material;

[0057] Step S2, the pre-burned material obtained in step 1 is mixed with sodium carbonate through a high-speed mixer to obtain a high-mix material, wherein the sodium content is 3% in excess; the high-mix material is placed in a box furnace, under an air atmosphere, with an air flow rate of 16 L / min, and the temperature is first increased to 900°C at a heating rate of 3°C / min, kept warm for 15 hours, and then naturally cooled to room temperature to obtain a burned material; the burned material is mechanically crushed and vibrated to obtain a B1 sample.

[0058] Comparative Example 2

[0059] This comparative example provides a double-point doped O3 sodium layered positive electrode material, the chemical formula of the double-point doped O3 sodium layered positive electrode material is [NaCa 0.001 ][Ni 0.333 Fe 0.333 Mn 0.334 Ti 0.001 ]O 2 , where Ca is the doping element for the sodium layer and Ti is the doping element for the transition metal layer.

[0060] The preparation method of the double-point doped O3 sodium layered positive electrode material comprises the following steps:

[0061] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn 0.334 (OH) 2 Pre-burning is performed, the pre-burning atmosphere is air, the pre-burning temperature is 550°C, the heating rate is 3°C / min, and the holding time is 6h to obtain a pre-burned material;

[0062] Step S2, the pre-burned material obtained in step 1 is mixed with sodium carbonate, calcium oxide and titanium oxide by a high-speed mixer to obtain a high-mixed material, wherein the sodium content is 3% in excess, the calcium metal content is one thousandth of the sodium content, and the titanium metal content is one thousandth of the transition metal content. The high-mixed material is placed in a box furnace under an air atmosphere with an air flow rate of 16 L / min, and the temperature is first increased to 900°C at a heating rate of 3°C / min, kept warm for 15 hours, and then naturally cooled to room temperature to obtain a fired material, and the fired material is mechanically crushed and vibrated to obtain a B2 sample.

[0063] Comparative Example 3

[0064] This comparative example provides a metal oxide coated synergistically modified O3 sodium layered positive electrode material, the metal oxide coated modified O3 sodium layered positive electrode material chemical formula NaNi 0.333 Fe 0.333 Mn 0.334 O 2 , the coating layer includes zirconium oxide.

[0065] The preparation method of the metal oxide coated modified O3 sodium layered positive electrode material comprises the following steps:

[0066] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn 0.334 (OH) 2 Pre-burning is performed, the pre-burning atmosphere is air, the pre-burning temperature is 550°C, the heating rate is 3°C / min, and the holding time is 6h to obtain a pre-burned material;

[0067] Step S2, the pre-burned material obtained in step 1 is mixed with sodium carbonate by a high-speed mixer to obtain a high-mix material, wherein the sodium content is 3% in excess, the high-mix material is placed in a box furnace, under an air atmosphere, the air flow rate is 16L / min, the temperature is first increased to 900°C at a rate of 3°C / min, the temperature is kept for 15 hours, and then naturally cooled to room temperature to obtain a first-burned material, the first-burned material is mechanically crushed, and vibrated and sieved to obtain a first-burned sample;

[0068] Step S3, weigh 100 kg of the calcined sample NaNi 0.333 Fe 0.333 Mn 0.334 O 2 , and 0.3kg of zirconium oxide were added into a high mixer and mixed at 3000r / min for 15min. The mixture was placed in a box furnace and heated to 650℃ at a heating rate of 3℃ / min under an oxygen atmosphere. The mixture was kept warm for 6h and naturally cooled to room temperature. The sodium layered positive electrode material B3 was sieved through a 300-mesh sieve.

[0069] Comparative Example 4

[0070] This comparative example provides a sodium layer point doped modified O3 sodium electric layer positive electrode material, the sodium layer point doped modified O3 sodium electric layer positive electrode material chemical formula [NaCa 0.001 ][Ni 0.333 Fe 0.333 Mn 0.334 ]O 2 , where Ca is the sodium layer doping element.

[0071] The preparation method of the sodium layer point doped modified O3 sodium electric layered positive electrode material comprises the following steps:

[0072] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn 0.334 (OH) 2 Pre-burning is performed, the pre-burning atmosphere is air, the pre-burning temperature is 550°C, the heating rate is 3°C / min, and the holding time is 6h to obtain a pre-burned material;

[0073] Step S2, the pre-burned material obtained in step 1 is mixed with sodium carbonate and calcium oxide through a high-speed mixer to obtain a high-mix material, wherein the sodium content is 3% in excess and the calcium metal content is one thousandth of the sodium content; the high-mix material is placed in a box furnace under an air atmosphere with an air flow rate of 16 L / min, and the temperature is first increased to 900°C at a heating rate of 3°C / min, kept warm for 15 hours, and then naturally cooled to room temperature to obtain a burned material; the burned material is mechanically crushed and vibrated to obtain a burned sample B4.

[0074] Comparative Example 5

[0075] The difference between this comparative example and the embodiment is that the sodium electrode layered positive electrode material B5 provided in this comparative example is only doped with the transition metal layer.

[0076] This comparative example provides a transition metal layer doped modified O3 sodium layered positive electrode material, the transition metal layer doped modified O3 sodium layered positive electrode material chemical formula is Na[Ni 0.333 Fe 0.333 Mn 0.334 Ti 0.001 ]O 2 , where Ti is the doping element for the transition metal layer.

[0077] The preparation method of the transition metal layer point-doped modified O3 sodium layered positive electrode material comprises the following steps:

[0078] Step S1: nickel iron manganese hydroxide Ni 0.333 Fe 0.333 Mn 0.334 (OH) 2 Pre-burning is performed, the pre-burning atmosphere is air, the pre-burning temperature is 550°C, the heating rate is 3°C / min, and the holding time is 6h to obtain a pre-burned material;

[0079] Step S2, the pre-burned material obtained in step 1 is mixed with sodium carbonate and titanium oxide through a high-speed mixer to obtain a high-mixed material, wherein the sodium content is 3% in excess and the titanium metal content is one thousandth of the transition metal content. The high-mixed material is placed in a box furnace under an air atmosphere with an air flow rate of 16 L / min. The temperature is first increased to 900°C at a heating rate of 3°C / min, kept warm for 15 hours, and then naturally cooled to room temperature to obtain a burned material. The burned material is mechanically crushed and vibrated to obtain a burned sample B5.

[0080] The sodium nickel iron manganate positive electrode materials prepared in the above Examples 1-3 and Comparative Examples 1-5 were subjected to pH and residual alkali tests, wherein the surface residual alkali test of the materials used water as the solvent. The results are shown in Table 1.

[0081] Table 1

[0082]

[0083]

[0084] Further, at 25°C, the sodium positive electrode materials prepared in the above Examples 1-3 and Comparative Examples 1-5 were respectively prepared into positive electrode sheets, and assembled with the metal sodium sheet negative electrode into CR2016 button batteries, and then the discharge current density was 150 mAg in the voltage range of 2.00-4.00 V. -1 The electrochemical performance test was carried out under , and the test results of the capacity retention rate after 200 cycles are shown in Table 2 below.

[0085] Table 2

[0086] Cathode Materials Capacity retention after 200 cycles (%) Example 1 A1 92.88 Example 2 A2 90.78 Example 3 A3 90.88 Comparative Example 1 B1 73.65 Comparative Example 2 B2 85.39 Comparative Example 3 B3 84.22 Comparative Example 4 B4 82.45 Comparative Example 5 B5 82.06

[0087] According to Table 1 and Table 2 above, the residual alkali of the single metal oxide coated layered sodium ion positive electrode material has decreased to varying degrees, and the effect is particularly obvious. The residual alkali has also decreased after double-point doping modification, but the relative decrease is not obvious, indicating that coating is the most effective means to reduce the residual alkali; it can be seen from Example 1 and Comparative Examples 1-3 that if no modification work is performed, or only a single double-point doping and a single metal oxide coating work are performed, the performance of the material cannot achieve the best performance. Example 1-3 realizes the synergistic modification of double-point doping and metal oxide coating, and the performance of the material can be greatly improved.

[0088] In summary, the present application achieves the following effects by realizing dual-point doping and coordinated metal oxide surface coating through the sodium layer and the transition metal layer: 1) The doping elements in the sodium layer play a supporting role in the sodium layer, stabilizing the interlayer spacing of the sodium layer before and after charging and discharging, making the charge and discharge curve of the battery smoother and improving the cycle performance of the material; 2) By incorporating high-priced elements into the transition metal layer, the phase change (O3'→P3') of the material during the charge and discharge process can be suppressed, the stability of the material can be improved, and the cycle performance of the material can be improved; 3) The metal oxide is coated on the surface of the material, so that the surface residual alkali of the positive electrode material decreases, effectively suppressing the occurrence of side reactions with the electrolyte, and thus improving the cycle performance of the material. The coating layer provides a protective layer to prevent the positive electrode material from directly contacting and reacting with moisture and carbon dioxide in the air, thereby improving the air stability of the material. 4) The process is simple and controllable, and easy to mass produce.

[0089] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0090] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A layered positive electrode material, characterized in that: The layered positive electrode material comprises a core and a coating layer located on the surface of the core; Among them, the chemical general formula of the core is [NaM b [Ni x Fe y Mn z N k O2], where 0 < b ≤ 0.1, 0.1 ≤ x ≤ 0.5, 0.1 ≤ y ≤ 0.5, 0.2 ≤ z ≤ 0.6, 0 < k ≤ 0.1, x + y + z = 1, M is the doping element of the sodium layer; N is the doping element of the transition metal layer; the coating layer is a metal oxide.

2. The layered positive electrode material according to claim 1, characterized in that The sodium layer doping element is any one or a combination of at least two metal elements having a radius close to that of sodium ions.

3. The layered positive electrode material according to claim 1, characterized in that The M is one or more of Ca, Mg, Sr, La, K, and Zn; and the N is one or more of Ti, Zr, Sb, Sc, Y, La, Ce, Sm, Ho, and Ta.

4. The layered positive electrode material according to claim 1, characterized in that 0 <b≤0.02;0<k≤0.01。 5. The layered positive electrode material according to claim 1, characterized in that The metal oxide is one or more of zirconium oxide, titanium oxide, tin oxide, magnesium oxide and tungsten oxide.

6. The layered positive electrode material according to claim 1 or 5, characterized in that: The metal element in the metal oxide accounts for 0.05%-0.5% of the mass of the core.

7. A method for preparing the layered positive electrode material according to claim 1, characterized in that: include: The pre-sintered nickel-iron-manganese hydroxide is uniformly mixed with a sodium source, a sodium layer doping element and a transition metal layer doping element, and subjected to a primary sintering treatment to obtain a single-sintered sample; The first-fired sample is crushed, uniformly mixed with metal oxides, and subjected to a second sintering treatment to obtain a layered positive electrode material.

8. The method for preparing a layered positive electrode material according to claim 7, characterized in that: The sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium nitrate, sodium acetate, and sodium citrate; the molar ratio of the sodium element in the sodium source to the sum of the nickel, iron, and manganese elements in the nickel-iron-manganese hydroxide is (1-1.04):

1.

9. The method for preparing a layered positive electrode material according to claim 7, characterized in that: The temperature of the pre-sintering treatment is 350-750°C, and the pre-sintering time is 3-9h; the temperature of the primary sintering treatment is 850-950°C, and the sintering time is 10-20h; the temperature of the secondary sintering treatment is 500-700°C, and the sintering time is 7-13h.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the layered positive electrode material according to any one of claims 1-6.

Citation Information

Patent Citations

  • Layered positive electrode material and preparation method and application thereof

    CN114843471A

  • Positive electrode material, preparation method thereof and sodium ion battery

    CN117317200A

  • High-crystallinity sodium ion battery positive electrode material and preparation method thereof

    CN117790735A

  • Low-residual-alkali-content layered oxide positive electrode material for sodium-ion battery and preparation method of low-residual-alkali-content layered oxide positive electrode material

    CN118398796A

  • Sodium battery high-voltage positive electrode material as well as preparation method and application thereof

    CN118919692A

Cited By

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN120998989A